Preparation method and application of electrolyte based on acetylacetonyl

By using acetylacetone homogeneous catalyst in lithium sulfur batteries, the problem of slow sulfur conversion reaction kinetics in lithium sulfur batteries is solved, and the effect of inhibiting the shuttle effect and improving the battery capacity and cycle stability is achieved.

CN119601768APending Publication Date: 2025-03-11SOUTHWEAT UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411693313.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The kinetics of sulfur conversion reaction in lithium-sulfur batteries are slow, resulting in a shuttle effect, loss of active substances, and reducing cycle stability.

Method used

Using an acetylacetone homogeneous catalyst, a homogeneous catalyst is constructed by dissolving the acetylacetone metal complex in the electrolyte, which promotes sulfur redox kinetics and inhibits the shuttle effect.

Benefits of technology

It effectively promotes sulfur redox kinetics, inhibits the shuttle effect, and improves the capacity and cycle stability of lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601768A_ABST
    Figure CN119601768A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new energy materials and devices, and discloses a preparation method and application of an electrolyte based on acetylacetonation.The preparation method comprises the steps that a compound containing acetylacetonato serves as a homogeneous catalyst to be dissolved and dispersed in a common electrolyte of a lithium-sulfur battery, the metal active center of the compound can be fully exposed, and the electrolyte containing acetylacetonato is obtained; the homogeneous catalysis function is realized. When the acetylacetone-based electrolyte is applied to the field of lithium-sulfur batteries and used as the positive electrode side electrolyte of the lithium-sulfur batteries, sulfur redox kinetics can be promoted, so that the shuttle effect is inhibited, the loss of active substances is reduced, and finally the capacity and cycle stability of the lithium-sulfur batteries are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials and devices, and in particular to a preparation method and application of an acetylacetone-based electrolyte. Background Art

[0002] The statements in this section merely provide background information related to the present disclosure and may not constitute prior art.

[0003] With the rapid development of electric vehicles, drones and mobile electronic devices, higher requirements are placed on high energy density energy storage systems. At present, traditional commercial lithium-ion batteries mainly use layered transition metal oxides or lithium iron phosphate as positive electrodes and graphite as negative electrodes. Their energy density is close to the theoretical value and it is difficult to meet the use needs. Therefore, it is of great significance to develop the next generation of energy storage systems with high energy density, long life and low cost.

[0004] Lithium-sulfur battery is an energy storage system that uses elemental sulfur as the positive electrode and metallic lithium as the negative electrode. It converts chemical energy into electrical energy through the electrochemical reaction between the positive and negative electrodes. Its theoretical specific energy is as high as 1675mAh g -1 , the theoretical energy density is 2600Wh kg -1 At the same time, the positive electrode material sulfur is abundant in nature and environmentally friendly, so it is regarded as one of the next generation of high energy density energy storage systems with application prospects. During the discharge process of the sulfur positive electrode, a series of polysulfides soluble in the electrolyte and the discharge end product Li2S / Li2S2 solid are produced. In the early stage of discharge, the sulfur positive electrode undergoes a reduction reaction to generate soluble Li2S8, Li2S6 and Li2S4 intermediates. Since the activation energy of the reaction is low, the reaction is relatively easy to proceed. Subsequently, Li2S4 is reduced to solid phase and poorly conductive Li2S2 / Li2S, resulting in a high reaction barrier and slow reaction rate in this stage, which makes the reaction kinetics of the discharge process slow, resulting in the accumulation of polysulfides. The generated polysulfides pass through the diaphragm to the negative electrode under the action of concentration gradient force and electric field force, and are reduced to short-chain polysulfides on the surface of the negative electrode, further forming insoluble Li2S2 and Li2S, which are deposited on the surface of the lithium negative electrode to form a passivation layer, resulting in a decrease in sulfur utilization and irreversible attenuation of the battery capacity.

[0005] Therefore, researchers have been exploring feasible solutions to better promote the kinetics of sulfur conversion reactions and thus suppress the shuttle effect. Past research work has mainly been based on the design of heterogeneous catalysts in terms of interface, defects, confinement and size to improve catalytic performance. However, heterogeneous catalysts cannot fundamentally solve the key problem of the full exposure of active sites at the catalytic interface and binding to the substrate during the catalytic process. The high activity, high selectivity and uniform structure of active centers of homogeneous catalysts have made them widely used in the petrochemical industry. Therefore, the homogeneous catalyst constructed by dissolving acetylacetonate-based metal complexes in the electrolyte is expected to solve the problem of slow sulfur conversion reaction kinetics in lithium-sulfur batteries, thereby suppressing the shuttle effect, increasing the capacity of lithium-sulfur batteries and improving the cycle stability of lithium-sulfur batteries.

[0006] In view of this, this application is hereby filed. Summary of the invention

[0007] The problem to be solved by the present invention is that the shuttle effect of lithium-sulfur batteries prepared based on ordinary electrolytes causes loss of active substances, resulting in poor cycle stability. The purpose of the present invention is to provide a preparation method and application of an acetylacetone-based lithium-sulfur battery electrolyte, which is used as a positive electrode electrolyte of a lithium-sulfur battery to achieve homogeneous catalytic conversion of polysulfides, thereby inhibiting the shuttle effect, reducing loss of active substances, and ultimately improving the capacity and cycle stability of lithium-sulfur batteries.

[0008] The present invention is achieved through the following technical solutions:

[0009] In a first aspect, the present invention provides the use of a compound containing an acetylacetonate group (-C5H8O2) as a homogeneous catalyst in a lithium-sulfur battery. Such a homogeneous catalyst can effectively promote sulfur redox kinetics, thereby inhibiting the shuttle effect.

[0010] According to a preferred embodiment, the compound containing acetylacetonate (-C5H8O2) is an acetylacetonate metal complex.

[0011] According to a preferred embodiment, the acetylacetonate metal complex includes at least one of vanadium acetylacetonate ([VO(acac)2]), manganese acetylacetonate (Mn(acac)2), and ferrous acetylacetonate (Fe(acac)2). These homogeneous catalysts can be dissolved in the electrolyte, fully exposing their metal active centers, realizing the function of homogeneous catalysis, effectively promoting sulfur redox kinetics, inhibiting the shuttle effect, reducing the loss of active substances, and ultimately improving the capacity and cyclic stability of lithium-sulfur batteries.

[0012] Another aspect of the present invention provides an acetylacetone-based electrolyte, wherein a homogeneous catalyst containing an acetylacetone group (-C5H8O2) is dissolved in the electrolyte.

[0013] Furthermore, the mass fraction of the homogeneous catalyst in the lithium-sulfur battery electrolyte is 0.05% to 0.5%, preferably 0.1%.

[0014] Furthermore, the lithium-sulfur battery electrolyte also includes lithium bis(trifluoromethane)sulfonamide (LiTSFI) and LiNO3 dissolved in a mixed solvent, and the mixed solvent includes DOL and DME. In addition, the homogeneous catalyst is also applicable to lithium-sulfur electrolytes of other formulations, such as the following formulation:

[0015] (1) 1.0 M LiTFSI was dissolved in a mixed solvent consisting of DME and DOL at a volume ratio of 1:1;

[0016] (2) 1.0 M LiTFSI was dissolved in a mixed solvent consisting of DME and DOL in a volume ratio of 1:1; 2.0% by mass of LiNO3 was also dissolved therein;

[0017] (3) 1.0 M LiTFSI was dissolved in a mixed solvent consisting of DME and DOL in a volume ratio of 1:1; 5.0% by mass of LiNO3 was also dissolved therein.

[0018] Another aspect of the present invention provides a method for preparing a lithium-sulfur battery electrolyte, comprising the following steps:

[0019] Step S1: dissolving and dispersing a compound containing acetylacetonate (-C5H8O2) as a homogeneous catalyst in a lithium-sulfur electrolyte.

[0020] According to a preferred embodiment, step S1 further includes stirring for 6.0 hours to allow the homogeneous catalyst to be fully dissolved in the electrolyte.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. On the one hand, the present application provides the application of acetylacetone-based compounds as homogeneous catalysts in lithium-sulfur batteries. Acetylacetone-based metal complexes are often used as promoters for curing agents such as acid anhydrides, dicyandiamide, organic hydrazides, and phenolic resins. With the development of chemical vapor deposition, some acetylacetone complexes with sublimable properties have been used to prepare high-temperature superconducting films; but their application in lithium-sulfur batteries has not been seen; the inventors of the present application have experimentally found that they can achieve the conversion kinetics of homogeneous catalysis of polysulfides and effectively inhibit the polysulfide shuttle effect;

[0023] 2. Using lithium-sulfur battery electrolyte prepared based on acetylacetone-based metal complexes to assemble lithium-sulfur batteries can improve the battery capacity and cycle stability of lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 CV curves of the lithium-sulfur batteries assembled in Examples 1-3 and Comparative Example 1;

[0025] Figure 2 The first cycle charge and discharge curves of the electrolytes prepared in Examples 1-3 and Comparative Example 1 at a current density of 0.5C;

[0026] Figure 3 The cycle performance diagram of the electrolyte prepared in Examples 1-3 and Comparative Example 1 at a current density of 0.5C;

[0027] Figure 4 The first cycle charge and discharge curves of the electrolytes prepared in Examples 1, 4, 5, and 6 at a current density of 0.5C;

[0028] Figure 5 Cyclic performance diagram of the electrolytes prepared in Examples 1, 4, 5, and 6 at a current density of 0.5C;

[0029] Figure 6 The diagram is a rate performance diagram of the electrolytes prepared in Examples 1-3 and Comparative Example 1 at different current densities. DETAILED DESCRIPTION

[0030] The specific embodiments listed in the present invention are only examples of the present invention, and the present invention is not limited to the specific embodiments described below. For those skilled in the art, any equivalent modifications and substitutions to the embodiments described below are also within the scope of the present invention. Therefore, the equal transformations and modifications made without departing from the spirit and scope of the present invention should be included in the scope of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturers are not specified for all reagents or instruments, they are all conventional products that can be purchased commercially. In order to better illustrate the present invention, numerous specific details are given in the specific embodiments below. It should be understood by those skilled in the art that the present invention can also be implemented without certain specific details. In other embodiments, the methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the purport of the present invention.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art. Unless otherwise specified, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0032] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0033] Example 1

[0034] A method for preparing a lithium-sulfur battery electrolyte comprises the following specific steps: dispersing 2.0 mg of vanadium acetylacetonate ([VO(acac)2]) in 2.0 g of a common lithium-sulfur battery electrolyte (the electrolyte is 1 M lithium bis(trifluoromethane)sulfonamide (LiTFSI) dissolved in a mixed solvent of DOL and DME in a volume ratio of 1:1, and contains 2.0% LiNO3), stirring in a glove box for 6 hours to fully dissolve it, and obtaining a lithium-sulfur battery electrolyte with a mass fraction of 0.1% of vanadium acetylacetonate.

[0035] Battery assembly: In a glove box with an argon atmosphere, assemble the positive electrode, diaphragm, lithium sheet, gasket, and spring in the order of 2032 button-type battery, and the electrolyte on the positive electrode side is the electrolyte prepared in Example 1.

[0036] Example 2

[0037] A method for preparing a lithium-sulfur battery electrolyte comprises the following specific steps: dispersing 2.0 mg of manganese acetylacetonate (Mn(acac)2) in 2.0 g of a common lithium-sulfur battery electrolyte (the electrolyte is 1 M lithium bis(trifluoromethane)sulfonamide (LiTFSI) dissolved in a mixed solvent of DOL and DME in a volume ratio of 1:1, and containing 2.0% of LiNO3), stirring in a glove box for 6 hours to fully dissolve it, and obtaining a lithium-sulfur battery electrolyte with a mass fraction of 0.1% of manganese acetylacetonate.

[0038] Battery assembly: In a glove box with an argon atmosphere, assemble the positive electrode, diaphragm, lithium sheet, gasket, and spring in the order of 2032 button-type battery, and the electrolyte on the positive electrode side is the electrolyte prepared in Example 2.

[0039] Example 3

[0040] A method for preparing a lithium-sulfur battery electrolyte comprises the following specific steps: dispersing 2.0 mg of ferrous acetylacetonate (Fe(acac)2) in 2.0 g of a common lithium-sulfur battery electrolyte (the electrolyte is 1 M lithium bis(trifluoromethane)sulfonamide (LiTFSI) dissolved in a mixed solvent of DOL and DME in a volume ratio of 1:1, and contains 2.0% LiNO3), stirring in a glove box for 6 hours to fully dissolve it, and obtaining a lithium-sulfur battery electrolyte with a mass fraction of 0.1% of ferrous acetylacetonate.

[0041] Battery assembly: In a glove box with an argon atmosphere, assemble the positive electrode, diaphragm, lithium sheet, gasket, and spring in the order of 2032 button-type battery, and the positive electrode electrolyte is the electrolyte prepared in Example 3.

[0042] Example 4

[0043] A method for preparing a lithium-sulfur battery electrolyte comprises the following specific steps: dispersing 2.0 mg of oxyvanadium acetylacetonate ([VO(acac)2]) in 4.0 g of a common electrolyte for a lithium-sulfur battery (the electrolyte is 1 M lithium bis(trifluoromethane)sulfonamide (LiTFSI) dissolved in a mixed solvent of DOL and DME in a volume ratio of 1:1, and contains 2.0% LiNO3), stirring in a glove box for 6 hours to fully dissolve it, and obtaining a lithium-sulfur battery electrolyte with a mass fraction of 0.05% of oxyvanadium acetylacetonate.

[0044] Battery assembly: In a glove box with an argon atmosphere, assemble the positive electrode, diaphragm, lithium sheet, gasket, and spring in the order of 2032 button-type battery, and the electrolyte on the positive electrode side is the electrolyte prepared in Example 4.

[0045] Example 5

[0046] A method for preparing a lithium-sulfur battery electrolyte comprises the following specific steps: dispersing 2.0 mg of vanadium acetylacetonate ([VO(acac)2]) in 1.0 g of a common lithium-sulfur battery electrolyte (the electrolyte is 1 M lithium bis(trifluoromethane)sulfonamide (LiTFSI) dissolved in a mixed solvent of DOL and DME in a volume ratio of 1:1, and containing 2.0% LiNO3), stirring in a glove box for 6 hours to fully dissolve it, and obtaining a lithium-sulfur battery electrolyte with a mass fraction of 0.2% of vanadium acetylacetonate.

[0047] Battery assembly: In a glove box with an argon atmosphere, assemble the positive electrode, diaphragm, lithium sheet, gasket, and spring in the order of 2032 button-type battery, and the electrolyte on the positive electrode side is the electrolyte prepared in Example 5.

[0048] Example 6

[0049] A method for preparing a lithium-sulfur battery electrolyte comprises the following specific steps: dispersing 5.0 mg of vanadium acetylacetonate ([VO(acac)2]) in 1.0 g of a common lithium-sulfur battery electrolyte (the electrolyte is 1 M lithium bis(trifluoromethane)sulfonamide (LiTFSI) dissolved in a mixed solvent of DOL and DME in a volume ratio of 1:1, and containing 2.0% LiNO3), stirring in a glove box for 6 hours to fully dissolve it, and obtaining a lithium-sulfur battery electrolyte with a mass fraction of 0.5% of vanadium acetylacetonate.

[0050] Battery assembly: In a glove box with an argon atmosphere, assemble the positive electrode, diaphragm, lithium sheet, gasket, and spring in the order of 2032 button-type battery and the electrolyte prepared in Example 6.

[0051] Comparative Example 1

[0052] The lithium-sulfur battery electrolyte used is: 1.0M LiTFSI in DME:DOL=1:1Vol%with2.0%LiNO3.

[0053] Battery assembly: In a glove box with an argon atmosphere, assemble the positive electrode, diaphragm, lithium sheet, gasket, and spring in the order of 2032 button-type battery and the electrolyte is the electrolyte provided in Comparative Example 1.

[0054] Performance Testing

[0055] The assembled button battery was placed in a constant temperature box at 20°C, and the cycle performance and rate performance of the assembled battery were tested using a battery testing system. The CV test voltage was 1.7-2.8V. In the cycle test, the current density was 0.2C (C=1675mAh / g). In the rate test, the current density increased in sequence of 0.5C, 1.0C, 2.0C, and 3.0C. Five cycles of charge and discharge were performed at each current density.

[0056] The application of the vanadyl acetylacetonate-based electrolyte in the lithium-sulfur battery of the present invention and the acetylacetonate-based metal complex realize the homogeneous catalytic conversion of polysulfides, inhibit the shuttle effect, and improve the electrochemical performance.

[0057] Figure 1 CV curves of the lithium-sulfur batteries organized in Examples 1-3 and Comparative Example 1. It can be seen from the figure that the redox peak of the lithium-sulfur battery using a homogeneous catalyst is sharper and higher, indicating that the sulfur conversion kinetics is faster during the charge and discharge process.

[0058] Figure 2 The first cycle charge and discharge curves of the electrolytes prepared in Examples 1-3 and Comparative Example 1 at a current density of 0.5C. It can be seen from the figure that the first cycle discharge specific capacities of Examples 1-3 are 810.7 mAh / g, 959.2 mAh / g, and 999.8 mAh / g, and the voltage differences of Examples 1-3 are all smaller than those of Comparative Example 1. This phenomenon indicates that the lithium-sulfur battery using a homogeneous catalyst has smaller resistance and polarization behavior.

[0059] Figure 3 The cycle performance diagram of the electrolyte prepared in Examples 1-3 and Comparative Example 1 at a current density of 0.5C. It can be seen from the figure that the capacity decay of the lithium-sulfur battery using the homogeneous catalyst is smaller. This is because the homogeneous catalyst accelerates the conversion of polysulfides and effectively improves the cycle stability of the lithium-sulfur battery.

[0060] Figure 4The first cycle charge and discharge curves of the electrolytes prepared in Examples 1, 4, 5, and 6 at a current density of 0.5C. It can be seen from the figure that the first cycle discharge specific capacities of Examples 1, 4, 5, and 6 are 810.7 mAh / g, 667.4 mAh / g, 913.4 mAh / g, and 787.1 mAh / g, respectively. This phenomenon indicates that the lithium-sulfur battery using a 0.1% acetylacetone-based homogeneous catalyst has smaller resistance and polarization behavior.

[0061] Figure 5 The cycle performance diagram of the electrolyte prepared in Examples 1, 4, 5, and 6 at a current density of 0.5C. It can be seen from the figure that the capacity decay of the lithium-sulfur battery using 0.1% acetylacetone-based homogeneous catalyst is smaller. This is because the homogeneous catalyst accelerates the conversion of polysulfides and effectively improves the cycle stability of the lithium-sulfur battery.

[0062] Figure 6 The rate performance diagram of the electrolyte prepared in Examples 1-3 and Comparative Example 1 at different current densities shows that the lithium-sulfur battery with the homogeneous catalyst has a higher specific capacity at high current density. At the same time, we can also observe that after high-rate charge and discharge, the lithium-sulfur battery using the homogeneous catalyst maintains a good capacity when it is restored to 0.5C rate. For example, the capacity of Example 1 at 0.5C, 1.0C, 2.0C and 3.0C is 813 mAh g –1 , 720mAh g –1 , 626mAh g –1 and 554mAh g –1 After high-rate charge and discharge, when it returns to 0.5C rate, it can still show 785mAh g –1 This phenomenon shows that the lithium-sulfur battery using homogeneous catalyst has excellent rate performance.

[0063] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.

Claims

1. Application of compounds containing acetylacetonate as homogeneous catalysts in lithium-sulfur batteries.

2. The use according to claim 1, characterized in that: The compound containing acetylacetonate is an acetylacetonate metal complex.

3. The use according to claim 2, characterized in that: The acetylacetonate-based metal complex includes at least one of vanadium acetylacetonate, manganese acetylacetonate, and ferrous acetylacetonate.

4. An acetylacetone-based electrolyte, characterized in that: The electrolyte contains 0.05% to 0.5% by mass of a homogeneous catalyst, which is a compound containing an acetylacetone group.

5. The acetylacetone-based electrolyte according to claim 4, characterized in that: The mass fraction of the homogeneous catalyst is 0.1%-0.2%.

6. The acetylacetone-based electrolyte according to claim 5, characterized in that: The mass fraction of the homogeneous catalyst is 0.1%.

7. An acetylacetone-based electrolyte according to any one of claims 4 to 6, characterized in that: The electrolyte also includes lithium bis(trifluoromethane)sulfonamide dissolved in a mixed solvent including DOL and DME.

8. An acetylacetone-based electrolyte according to claim 7, characterized in that: The electrolyte also includes LiNO3.

9. The acetylacetone-based electrolyte according to claim 8, characterized in that: The mass fraction of the LiNO3 is 2.0%-5.0%.

10. The method for preparing an acetylacetone-based electrolyte according to claim 9, characterized in that: The steps include: Step S1: dissolving and dispersing a compound containing acetylacetone groups as a homogeneous catalyst in a common electrolyte of a lithium-sulfur battery.